2002
DOI: 10.4141/p01-106
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method to detect Cryptolestes ferrugineus (Coleoptera: Cucujidae) larvae in stored grain

Abstract: . 2002. A rapid method to detect Cryptolestes ferrugineus (Coleoptera: Cucujidae) larvae in stored grain. Can. J. Plant Sci. 82: 591-597. Modifications of three detection methods, based on the heat-gradient principle employed by the Berlese funnel method were investigated to extract larvae of the rusty grain beetle, Cryptolestes ferrugineus (Stephens), developing under the seed coats of infested kernels in grain samples. Onekilogram samples of wheat, barley and corn were artificially infested with rusty grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
5
1
Order By: Relevance
“…This explains why both old and young larvae were extracted by microwave method with no significant difference (Table 1). This study found the Berlese funnel method could recover more old larvae than young larvae, which is inconsistent with the report by Minkevich et al (2002). This contradiction might be caused by different setups such as the distances between lamp and grain surface and depths of grain inside Berlese funnels.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…This explains why both old and young larvae were extracted by microwave method with no significant difference (Table 1). This study found the Berlese funnel method could recover more old larvae than young larvae, which is inconsistent with the report by Minkevich et al (2002). This contradiction might be caused by different setups such as the distances between lamp and grain surface and depths of grain inside Berlese funnels.…”
Section: Discussioncontrasting
confidence: 78%
“…This result indicated that the heat produced by either the microwaves or incandescent light bulb was the same on the effectiveness of forcing larvae out of grain kernels (Smith, 1977;Minkevich et al, 2002;Jian et al, 2014a). The higher recovery percentage associated with the microwave treatment was caused by the shaking and mixing during microwave treatment after larvae escaped out of grain kernels.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations